Terrorism as non-conventional security threat - Zirojević Mina (Međunarodni Problemi, 2008)
Endeavoring to establish the essence and the basic structural characteristics of the contemporary forms of terrorism the author firstly analyses different attempts to define the phenomenon itself as one of the most significant forms of the non-unconventional security threats. The paper points to different motives and objectives (political, social and other) of some actors that belong to various terrorist groups and organizations acting in the world today. In that regard, the approach of the states and international factors to this challenge should be different. As the author concludes that the results that have been achieved so far in the 'war on terror', as well as the consequences resulting from solely applying repression and the principle of non negotiation with terrorists, are such that should be critically reconsidered.